The perception of packaging free in everyday life - Bencsik, Csilla; Káposzta, József (Studia Mundi – Economica, 2022)
In recent years, sustainability and education for sustainability have become more and more widespread. Unfortunately, the world faces many challenges in this regard. These include unsustainable consumption and production, climate change and the ever-increasing pollution of the Earth. As a result, we should be paying more and more attention to environmental protection, putting more and more products from sustainable agriculture on the shelves, using more and more environmentally friendly packaging and, along with this, making more and more efforts to replace finite energy sources with renewable energy sources. From an environmental sustainability perspective, the reality is that mountains of waste are floating in the oceans, more and more genetically modified crops are entering the food chain, experts are talking about programmed obsolescence, and energy use is increasing.For all these reasons, the aim of our study is to provide a comprehensive picture of the packaging-free movement, its perception and future prospects. In our research, we will examine people's knowledge of recyclability, the extent to which they take into account the material used for the packaging of the goods they buy, the form and extent of waste separation and their perception of the future potential of packaging-free packaging.